Diseño de una blonda a partir del aprovechamiento de almidón de yuca. Villavicencio-Meta. (2020)
The department of Meta is one of the largest cassava producers in Colombia, highlighting one of the great properties of sweet cassava, which has a high percentage of glucose, achieving exceptional flexibility and hardness to generate an alternative to excessive demand for single-use expanded polystyrene such as doilies; This is why the Design of a lace was generated from the use of cassava starch. For the development of this research, 4 stages were proposed; Initially, we started with a base composition as a result of a documentary search to carry out what would be the obtaining of a biopolymer, describing the step-by-step for obtaining it. This procedure was carried out in a laboratory report. After obtaining the biopolymer, a matrix was proposed with the results of 20 tests in which the components were modified, highlighting in the drying process the% of humidity obtained in the shortest time, from this laboratory practice it was determined that 2 different types of composition that managed to have a humidity of 25% in the shortest time 3 models of different dimensions of each composition were established, the samples were analyzed for flexural properties, humidity, hardness and density to obtain a 70/30 composition of the starch cassava versus fiber reinforcement fique. Finally, a cost table was made to know the total cost of obtaining each of the 3 lace models (15cm, 20cm and 25cm) and to generate a competitive alternative option for the plastics industry to reduce the excessive use of polystyrene. expanded single use, making a great contribution to the decontamination of the planet.